Development of Mechanical Learning Media Based on Google Sites in Basic Engineering Subjects for Grade X Vocational High School - Dido Febriananda Nosa; Junil Adri; Febri Prasetya; Andril Arafat (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aims to develop a web-based learning media using Google Sites, named Mechanical Learning, for Basic Engineering subjects in Grade X Vocational High School. The research was motivated by the limited use of technology in learning and teacher-centered instructional practices. This study employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects consisted of material experts, media experts, and students. Data were collected through validation questionnaires, practicality questionnaires, and learning outcome tests. Data analysis used descriptive statistics and N-Gain analysis. The results showed that the developed media is highly valid, with material validation scores of 4.49 and 4.30, and media validation scores of 4.75 and 4.60. The practicality test showed an average score of 4.47 (very practical), while the effectiveness test showed an N-Gain of 70.68% (moderately effective). Therefore, Mechanical Learning media is valid, practical, and effective to support learning outcomes.